Planning in the inventory management: analysis in companies of the sector of industrial security - Moronta Uribe, Yocelyn Haidee
The objective of this article was to analyze inventory management in companies in the industrial security sector of the Maracaibo municipality. Descriptive, non-experimental, transectional methodology was used, the population was made up of procurement and   warehouse personnel of the companies active in the National Registry of Contractors (RNC) (2017), which have the sale of Security products as fiscal activity Industrial. The results obtained allow us to conclude that inventory management planning presents a good level within the companies in the sector, so it is recommended to use it, in future studies, as a reference to assess the situation.